2020
DOI: 10.1364/oe.397502
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the upper limits of the local density of states via optimized metallic cavities

Abstract: By computational optimization of air-void cavities in metallic substrates, we show that the local density of states (LDOS) can reach within a factor of ≈10 of recent theoretical upper limits and within a factor ≈4 for the single-polarization LDOS, demonstrating that the theoretical limits are nearly attainable. Optimizing the total LDOS results in a spontaneous symmetry breaking where it is preferable to couple to a specific polarization. Moreover, simple shapes such as optimized cylinders attain nearly the pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…for topology optimization (Liang and Johnson 2013;Wang et al 2018;Yao et al 2020). More generally, this situation corresponds to the correlation matrix being low-rank: if is rank K, we can compute the trace in K solves.…”
Section: Trace Computation: Few Input Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…for topology optimization (Liang and Johnson 2013;Wang et al 2018;Yao et al 2020). More generally, this situation corresponds to the correlation matrix being low-rank: if is rank K, we can compute the trace in K solves.…”
Section: Trace Computation: Few Input Channelsmentioning
confidence: 99%
“…In this particular case, after examining a large number of local optima (not shown), we found that the best local optimum is simply a circular disk with a particular radius. The existence of many local optima with performance varying by factors of 2-5 is not unusual in wave problems (Yao et al 2020;Diaz and Sigmund 2010;Bermel et al 2010), and while various heuristic strategies have been proposed to avoid poor local minima (Mutapcic et al 2009; Aage and Egede Johansen 2017; Bermel et al 2010;Schneider et al 2019) beyond simply probing multiple random starting points, the only way to obtain rigorous guarantees is to derive theoretical upper bounds (Miller et al 2016;Yao et al 2020) as discussed further in Sect. 5 (purely numerical global search can generally provide practical guarantees only for very low-dimensional Maxwell optimization Azunre et al 2019).…”
Section: Fluorescent Particlementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for wavelength-scale patterning, the open questions are two-fold: will the larger size scale of the patterning relieve the stringent feature-size constraints imposed by effective-medium theory and, in tandem, will it enable substantially larger HTCs and RHT rates beyond the values predicted here? Given the significant recent work in both large-scale, computational “inverse design”, as well as analytical and computational bounds to optical response, ,,, conclusively answering such questions should be feasible in the near future.…”
Section: Looking Forwardmentioning
confidence: 99%
“…One trivial special case in which the trace computation drastically simplifies is that of only a few sources or a few input channels, most famously in the case of the local density of states (LDOS): emission by a molecule at a single location in space but with a random polarization [1,24]. In the case of LDOS, this reduces the trace computation to three Maxwell solves, one per principal polarization direction, making the problem directly tractable for topology optimization [47][48][49]. More generally, this situation corresponds to the correlation matrix B being low-rank: if B is rank K, we can compute the trace in K solves.…”
Section: Trace Computation: Few Input Channelsmentioning
confidence: 99%